Sperm lacking Bindin are infertile but are otherwise indistinguishable from wildtype sperm - Gary M. Wessel (Nature Portfolio, 2021)
Abstract Cell–cell fusion is limited to only a few cell types in the body of most organisms and sperm and eggs are paradigmatic in this process. The specialized cellular mechanism of fertilization includes the timely exposure of gamete–specific interaction proteins by the sperm as it approaches the egg. Bindin in sea urchin sperm is one such gamete interaction protein and it enables species–specific interaction with a homotypic egg. We recently showed that Bindin is essential for fertilization by use of Cas9 targeted gene inactivation in the sea urchin, Hemicentrotus pulcherrimus. Here we show phenotypic details of Bindin-minus sperm. Sperm lacking Bindin do not bind to nor fertilize eggs at even high concentrations, yet they otherwise have wildtype morphology and function. These features include head shape, tail length and beating frequency, an acrosomal vesicle, a nuclear fossa, and they undergo an acrosomal reaction. The only phenotypic differences between wildtype and Bindin-minus sperm identified is that Bindin-minus sperm have a slightly shorter head, likely as a result of an acrosome lacking Bindin. These data, and the observation that Bindin-minus embryos develop normally and metamorphose into normal functioning adults, support the contention that Bindin functions are limited to species–specific sperm–egg interactions. We conclude that the evolutionary divergence of Bindin is not constrained by any other biological roles.